2020
DOI: 10.1002/aenm.202000765
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Flexible Organic Solar Cells

Abstract: Extensive efforts have been devoted during the last decade to organic solar cell research that has led to remarkable progress and achieved power conversion efficiencies (PCEs) in excess of 10%. Among the existing flexible organic solar cells, ultrathin organic solar cells with a total thickness <10 µm have important advantages, including good mechanical bending stabilities and good conformability. These advantages have led to power generation solutions for wearable electronics. In this essay, the progress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
315
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 519 publications
(344 citation statements)
references
References 84 publications
0
315
0
2
Order By: Relevance
“…Although previous studies have demonstrated excellent flexural endurance of QD photovoltaics 37 , 38 , none have demonstrated high PCEs, probably due to poor charge transfer and carrier extraction efficiencies at QD heterointerfaces and interfaces. PCEs of flexible QD photovoltaics have been limited to below 10% 38 , which lag significantly behind flexible organic and thin-film perovskite solar cells 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated excellent flexural endurance of QD photovoltaics 37 , 38 , none have demonstrated high PCEs, probably due to poor charge transfer and carrier extraction efficiencies at QD heterointerfaces and interfaces. PCEs of flexible QD photovoltaics have been limited to below 10% 38 , which lag significantly behind flexible organic and thin-film perovskite solar cells 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…OPVs are therefore promising for versatile terrestrial and outer space applications. [1][2][3][4][5][6][7][8][9][10][11] Currently, nonfullerene acceptors, especially fused-ring electron acceptors (FREAs), are a research hotspot of BHJ OPVs, setting new records of power conversion efficiencies (PCEs). [12][13][14][15][16][17][18][19][20] Unlike fullerene derivatives (eg, PC 61 BM and PC 71 BM), FREAs offer the advantages of low cost, flexible adjustment of optoelectronic properties, strong absorption in the visible and near-infrared region.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated excellent exural endurance of QD photovoltaics, [37][38] none have demonstrated high PCEs, probably due to poor charge transfer and carrier extraction e ciencies at QD heterointerfaces and interfaces. PCEs of exible QD photovoltaics have been limited to below 10%, 38 which lag signi cantly behind exible organic and thin-lm perovskite solar cells [39][40] .…”
Section: Introductionmentioning
confidence: 99%